LES ROCHES MAGMATIQUES ET PYROCLASTIQUES DU CONGLOMERAT STRUNIEN DE L’OUED TIFLET (MESETA NORD OCCIDENTALE MAROCAINE): PETROGRAPHIE, GEOCHIMIE ET PROVENANCE - El Haibi, Hind; El Hadi, Hassan; Tahiri, Abdelfatah; Bensalah, Ibtissam; El Maidani, Ayoub (European Scientific Journal, ESJ, 2015)
In the north boundary of the Sidi Bettache basin (northwestern morrocan Meseta), the strunian period is characterized by coarse detrital sedimentation, among them the limestone conglomerate of Tiflet river. This conglomerate is rich in magmatic pebbles varying by nature and shape. Petrographical and geochemical studies allow distinguishing eleven facies, which generally correspond to basic, including gabbros, intermediate or acids rocks. Tuffs, sulfides bearing-rocks and oxides are also identified. Age of this magmatic rocks is discussed.